2010
DOI: 10.1159/000314036
|View full text |Cite
|
Sign up to set email alerts
|

Ductus Venosus in the First Trimester: Contribution to Screening of Chromosomal, Cardiac Defects and Monochorionic Twin Complications

Abstract: In the first trimester the ductus venosus can be easily identified with color Doppler and a ductus venosus waveform can be obtained by pulsed Doppler. At 11–13 weeks the prevalence of abnormal a-wave in the ductus venosus is inversely related to fetal crown-rump length and maternal serum pregnancy-associated plasma protein-A (PAPP-A), increases with fetal nuchal translucency (NT) thickness and is more common in women of Black racial origin and in fetuses with abnormal karyotype or cardiac defects. Ductus venos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 79 publications
1
52
0
4
Order By: Relevance
“…Maiz and Nicolaides reported that an abnormal flow in the DV was observed in 69.1% of trisomy 21 fetuses, and in 3.7% of chromosomally normal fetuses [5,17]. First reports of the use of the DV flow assessment in trisomy 21 screening have been published in 1990's [16].…”
Section: Discussionmentioning
confidence: 99%
“…Maiz and Nicolaides reported that an abnormal flow in the DV was observed in 69.1% of trisomy 21 fetuses, and in 3.7% of chromosomally normal fetuses [5,17]. First reports of the use of the DV flow assessment in trisomy 21 screening have been published in 1990's [16].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that serum PLGF and AFP are useful in first-trimester screening for preeclampsia, fetal growth restriction and preterm birth [16,17,18]. Similarly, measurement of DV PIV can improve the performance of screening for trisomies and it is also useful in screening for major cardiac defects [7,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these metabolites are useful in first-trimester screening for preeclampsia, fetal growth restriction and preterm birth [26,27,28]. Measurement of DV PIV can improve the performance of screening for trisomies considerably and it is also useful in screening for major cardiac defects [29,30,31]. However, competence in this examination requires extensive experience in the 11- to 13-week scan and specific training [32]; the test is at present carried out in specialist centres and is unlikely to be used universally in first-line screening.…”
Section: Discussionmentioning
confidence: 99%